Weathering and soil properties on catenary sequences in forest and alpine ecosystems of the central Rocky Mountains - Bergstrom, Robert Mark, author; Kelly, Eugene F., advisor; Rhoades, Charles C., committee member; Borch, Thomas, committee member; Melzer, Suellen, committee member; Martin, Patrick H., committee member (Colorado State University. Libraries, 2017)
The evolution of soil landscapes can be evaluated by studying soil properties along catenary sequences—soil sequences that are hydrologically and topographically connected along hillslopes from higher elevation to lower elevation. Using the catena model, I investigated the manifestation of soil forming factors in conditioning weathering and soil development in the Mountain Ecosystems of the Fraser Experimental Forest (FEF), Colorado. The research outlined and presented in this dissertation is preceded by a short narrative on soil forming properties, hillslope models, and assessing weathering in soils. The work presented in this dissertation is a result of a multidisciplinary framework for pedological research, derived from the integration of and consideration of pedology, geomorphology, and hydrology. The future of pedological research will involve the assimilation of multidisciplinary approaches and thinking. This dissertation elucidates on (1) the distribution of soil properties along soil catenas and their implication for hydrologic and biogeochemical linkages across landscapes, (2) the evaluation of chemical alteration thru modeling soil strain along soil catenas, (3) the quantification and distribution of soil elemental fluxes along soil catenas, and (4) the determination of the contributions of weathering and atmospheric inputs to landscapes at FEF. My field sites were located in FEF, a model site of the alpine and forested environments of the central Rocky Mountains. The FEF is an ideal setting to study the interaction of soil forming factors in complex mountain terrain. A combination of traditional and more modern methods to explore the linkages between soil properties along mountain catenas were employed in order to gain insight into soil landscape evolution in complex mountain terrain. I established eight catenas along relatively steep mountain hillslopes while constraining the lithologic differences along the soil landscapes. Vegetative changes along these catenas could not be ignored; rather, the differences provided insight into the influence of vegetative cover on soil properties. Soils were sampled along the catenas, beginning in the mountaintop landscapes (crests or summit) and ending in the mountainbase landscapes, where wetlands along riparian corridors dominate. Soil morphology and soil chemistry along the catenas provided understanding into the evolution of soil landscapes at FEF and their connectedness to the hydrologic flowpaths along these hillslopes. Results suggested that these soil landscapes are in various states of evolution, marked by the relative development of illuvial and elluvial horizons, and that the landscapes are dominated by subsurface lateral flow. The data also suggested that atmospheric deposition may be an important contributor to pedogenesis in these landscapes and that there are expected hot-spots of nutrient accumulations in the mountainbase landscapes, where upland soils have transported and deposited dissolved ions and fine soil particles into wetland soils along riparian corridors. The next question became: does the distribution of elements along soil landscapes reflect what was expected from the aforementioned analyses and is the fate of elements controlled by the landscape positions? What is the balance between the atmospheric contributions to weathering and internal cycling of cations? Subsequently, the analysis for soils along the catenas was extended to model soil strain within the soil landscapes, quantify mass fluxes and distribution of elements within the soil landscapes, and quantify the atmospheric contributions to weathering in these systems. Results indicated that dilation in upper soil horizons reflect the textural patterns in the same horizons across all landscapes—supporting the notion that the soils along theses catenas have been strongly influenced by additions via atmospheric deposition, and this influence is detectable across entire hillslopes. Also, modeled soil strain indicated that great pedogenic additions have occurred in the mountainbase landscapes—supporting the notion that dissolved ions and fine soil material have been transported and deposited downslope via subsurface lateral flow. Calculated elemental flux values indicated that soil nutrients originating the upland landscape positions are transferred to lower landscapes through the mountainflanks, and are deposited in the mountainbase landscapes, where the soils were found to be enriched in the following major elements—Ca, Na, K, Al, Fe, and Mg. In turn, the impact of atmospheric contributions to soil landscapes along a catena was revealed. The data suggested that surface soil horizons are more strongly influenced by atmospheric contributions than subsurface horizons. Likewise, subsurface horizons are increasingly more influenced by the weathering of parent material moving from higher soil landscapes to lower soil landscapes. Lastly, results suggest that the isotopic signature within mountaintop soil landscapes is coupled to vegetative cover and snowfall and snowmelt hydrology dynamics. The soil catena model endures as a framework for providing insight into the relationships of soil forming factors across gradients of variation.
Keywords: pedology; weathering; soil; catena